2019
DOI: 10.3928/01913913-20190206-01
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Medial Rectus Recession With Adjustable Suture in Acute Concomitant Esotropia of Adulthood

Abstract: Purpose: To review and analyze the surgical outcomes of bilateral medial rectus recession with adjustable suture in acute concomitant esotropia of adulthood (ACEA). Methods: The charts of all adults diagnosed as having ACEA between 2004 and 2017 were reviewed. Best corrected visual acuity, refractive error, ocular alignment measured in prism diopters (PD), and stereopsis were examined at presentation, 1 day postoperatively, and final follow-up visit (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There are many treatment options for AACE [10,[33][34][35][36] . Previous research has suggested that strabismus surgery for AACE can successfully improve diplopia and restore good binocular function in patients who do not have underlying intracranial problems [37][38][39][40] . In AACE, surgical approaches include unilateral medial rectus recession and lateral rectus (R&R) resection, bilateral medial rectus recession, or bilateral LR resection.…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatment options for AACE [10,[33][34][35][36] . Previous research has suggested that strabismus surgery for AACE can successfully improve diplopia and restore good binocular function in patients who do not have underlying intracranial problems [37][38][39][40] . In AACE, surgical approaches include unilateral medial rectus recession and lateral rectus (R&R) resection, bilateral medial rectus recession, or bilateral LR resection.…”
Section: Discussionmentioning
confidence: 99%
“…BMR and unilateral R&R are the most common surgical procedures performed in patients with AACE. [3,5,6] The surgical outcomes of AACE are relatively favorable compared with those of other types of esotropia. [5] In this study, all patients who underwent surgery showed an improvement in diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Prior published literature has provided details on classifications based on hypothetical mechanisms, the role of neuroimaging, and surgical outcomes. [2][3][4][5][6][7] AACE without intracranial lesions may not be a life-threatening condition. However, esotropia and diplopia cause discomfort and anxiety and can decrease the quality of life in patients with AACE.…”
Section: Introductionmentioning
confidence: 99%